2020
DOI: 10.15244/pjoes/109720
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calcium on the Alleviation of Cadmium Toxicity in <i>Salix matsudana</i> and Its Effects on Other Minerals

Abstract: Cadmium (Cd) is a highly toxic trace element mainly derived from industrial processes and phosphate fertilizers [1]. Cd concentrations in soil near smelters are extremely high, up to 200 mg/kg [2]. Considerable attention has been attached to problems associated with Cd pollution, with the development of modern industry and agriculture. It is a non-essential heavy metal with high toxicity to plants, animals and humans [3] and has been regarded as most dangerous environmental pollutant [4]. Cd is of great concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
(39 reference statements)
1
7
0
Order By: Relevance
“…TF value > 1, that is to say, large amounts of Pb are transported to the shoots from the roots, which differs from other plants, including Allium sativum, Ricinus communis, Brassica juncea, Neyraudia reynaudiana, and some other willow clones, in which, large amounts of Pb ions are accumulated in the roots and small amounts are transported to the shoots after Pb stress [13,14,25,34,35]. Nevertheless, some studies have reported on the use of crop plants and forest plants, including poplar and willows, to remove heavy metals from contaminated soils [22,23,26,[36][37][38][39][40]. Other investigations indicated that hyperaccumulators, plants that accumulate heavy metals from the soil into their shoots, are immensely useful in phytoextraction [23,36].…”
Section: Discussionmentioning
confidence: 99%
“…TF value > 1, that is to say, large amounts of Pb are transported to the shoots from the roots, which differs from other plants, including Allium sativum, Ricinus communis, Brassica juncea, Neyraudia reynaudiana, and some other willow clones, in which, large amounts of Pb ions are accumulated in the roots and small amounts are transported to the shoots after Pb stress [13,14,25,34,35]. Nevertheless, some studies have reported on the use of crop plants and forest plants, including poplar and willows, to remove heavy metals from contaminated soils [22,23,26,[36][37][38][39][40]. Other investigations indicated that hyperaccumulators, plants that accumulate heavy metals from the soil into their shoots, are immensely useful in phytoextraction [23,36].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of Ca effectively alleviated Cd toxicity in Cd-treated plants. A previous study indicated a internal mechanism for depressing the Cd toxicity as Ca concentrations increased in plant roots exposed to Cd, that when both Cd and Ca exist in the soil system, Ca and Cd exhibit similar chemical properties, Ca competes with Cd at adsorption sites in the soil, as a result, Cd uptake is reduced by Ca, then reducing Cd toxic effects in plants [7,13,20,23]. µM Cd.…”
Section: Ca Addition Alleviated CD Physiological Toxicitymentioning
confidence: 99%
“…Hayakwa et al [20] indicated that Ca could inhibit Cd transport from the roots to stems and leaves. In a previous investigation, 5 mM Ca alleviated the toxic effects of Cd on S. matsudana seedling growth and promoted the uptake of copper (Cu), iron (Fe), zinc (Zn), and manganese (Mn) to different degrees [7]. However, the Ca mechanism that affects Cd accumulation in plants remains to be Previous studies demonstrated that heavy metal subcellular localization, chemical forms and their mobility may be related to heavy metal detoxification and tolerance in plants [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Analuddin's research showed that mangroves were suffering from serious cadmium and zinc pollution, and mangroves could tolerant to various metals pollution in their environment (Analuddin et al 2017, Sundaramanickam et al 2016). Cadmium (Cd) is a widely existed nonessential element, which is classi ed as a harmful heavy metal to human health (Chao et al 2009, Shang et al 2020).…”
Section: Introductionmentioning
confidence: 99%